Ethical Challenges in Preparing for Bioterrorism: Barriers Within the Health Care System - Wynia, Matthew K. (© American Journal of Public Health 2004, 2004)
Preparedness for bioterrorism poses significant ethical challenges. Although public health ethics and preparedness have received attention recently, health care ethics must also be considered. In epidemics, the health care system assists public health in 3 tasks: detection, containment, and treatment. Detection might fail if all patients do not have access to care, or if physicians do not understand their obligation to report infectious diseases to public health authorities. Containment might fail if physicians view themselves only as advocates for individual patients, ignoring their social obligations as health professionals. Treatment might fail if physicians do not accept their professional duty to treat patients during epidemics. Each of these potential ethical barriers to preparedness must be addressed by physicians and society.